AMERICAN DREAM IN "THE GREAT GATSBY" BY F. SCOTT FITZGERALD - Kaeng, Geby; Andries, Fivy; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The American dream depicted in the novel The Great Gatsby by Francis Scott Fitzgerald is the subject of this study. The American Dream is centered on success ambition, and in The Great Gatsby, the main character strives for greater heights than he has ever been. The author used qualitative research to examine the research's issue. The author used sociological proposition to analyze the novel for this study. A collection of ideas that provide an explanation for human society is known as a sociological proposition. Priorities, perspectives, and the data they define as significant are all important to propositions. Consequently, they present a specific and partial view of reality. There are a number of criteria that can be used to group sociological propositions together. The distinction between social action propositions and structural action propositions is the most significant of these. According to the structural proposition, the structure of our society is created by a network of connections. Our lives and characters are shaped by this structure. Underneath the facade of western individualism's free existence are structured sets of social connections. The particular set of structural laws that are in effect in any given society is the primary focus of structuralism.